Copper(I)-Promoted C–N Cross-Coupling of N-Heterocyclic Compounds with 1,2-Di(pyrimidin-2-yl) Disulfides - Wei, Kai-Jie; Quan, Zheng-Jun; Zhang, Zhang; Da, Yu-Xia; Wang, Xi-Cun (Synlett, 2016)
A CuTC-promoted C–N cross-coupling of 1,2-di(pyrimidin-2-yl) disulfides with N-heterocyclic compounds including indoles, triazole benzotriazole, and benzoimidazole by C–S cleavage of the disulfides is reported.
Keywords: N-heterocycles; indoles; disulfides; CuTC; C–N cross-coupling